Technologieorientierte Industrien und Unternehmen: Alternative Definitionen - Eric A. Nerlinger; Georg Berger (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1995)
During the last years more and more discussions came up about the contribution of technology-oriented and technology-intensive industries for employment and economic development. One reason for some of the contradictory evaluations of technology-intensive industries can be attributed to different conceptual definitions of technology and high-technology. This paper examines various definitions of high-technology, ranging from input factors, output factors, mixed input-output factors. subjective evaluations to definitions, based on employment or turnover growth. After characterizing the advantages and disadvantages of each factor, relevant definitions of high-technology are then discussed in detail. One finding of this overview is, that there's a huge mass of definitions which make more or less sense, depending on the underlying data, definitions and thresholds.
Keywords: 330; Hochtechnologiesektor; Industrie; Wirtschaftsindikator; Forschungskosten; Wissenschaftler; Patent; Unternehmenswachstum; Theorie